Influence of the modulator and inhibitor of TLR4 on biochemical indexes in a pulp of cutters of rats (LLC "Endo Press", 2020)
In a model experiment reaction of a pulp of cutters of rats to introduction of melatonin and an inhibitor of TLR4 was studied. It is established that introduction of melatonin stimulates activity of AST and LDH in a pulp of cutters of experienced rats. Introduction of an inhibitor of TLR4 activates AST to a large extent and suppresses LDH. Activity of ALP in a pulp of cutters of rats in response to melatonin increases in a pulp of the top cutters and goes down in a pulp of the lower cutters. In case of introduction of the antagonist of TLR4, inversely proportional changes in activity of ALP in a pulp of cutters are observed. Shifts in the quantitative composition of IL-6 and TNF-α were more essential at introduction of an inhibitor of TLR4.